Early‐stage breast cancer and employment participation after 2 years of follow‐up: A comparison with age‐matched controls - Christine C. Ekenga; Maria Pérez; Julie A. Margenthaler; Donna B. Jeffe (Cancer, 2018)
BACKGROUND Although cancer survivors are more likely to be unemployed than individuals without a cancer history, employment participation after treatment of early‐stage breast cancer has not been widely studied to date. The objectives of the current study were to evaluate employment trajectories in a cohort of patients with early‐stage breast cancer and age‐matched controls from the time of diagnosis to the 2‐year follow‐up, and identify factors associated with diminished and emerging employment participation. METHODS As part of a larger cohort study of 1096 patients with early‐stage breast cancer and same‐aged women without breast cancer, data from 723 working‐age (aged 40‐64 years) women (347 patients and 376 controls) were analyzed to evaluate 4 employment trajectories (sustained unemployment, diminished employment, emerging employment, and sustained employment). Multivariable logistic regression models were used to identify factors associated with diminished employment versus sustained employment, and emerging employment versus sustained unemployment. RESULTS Lower percentages of patients (71%) compared with controls (79%) reported full‐time or part‐time employment at enrollment ( P